Josefa Ignacia de Meñaca Batiz y Aréchaga, fundadora de “La Enseñanza”, de Las Hijas de la Caridad, en Los Arcos (Navarra) - Pastor Abáigar, Víctor (Huarte de San Juan. Geografía e Historia, 2007)
The purpose of this work is primarily to present some biographical infomation about doña Josefa Ignacia de Meñaca Batiz y Aréchaga who was born in Bilbao and founded “La Enseñanza” (Education) in Los Arcos (Navarre). This charitable/educational foundation commended her to Saint Vincent de Paul’s Sisters of Charity in 1828. Since the objective was to improve the precarious position of education in the town at that time, we show how education developed from the sixteenth century, from when documents prove its existence, up to the arrival of the nuns and the influence they have had on the town’s education over one hundred and fifty years. Due to the fact that this happened thirty years after the French Revolution, and that for historical and geographical reasons our town was so involved in the French occupation, we have recorded certain aspects which affected the development in education. Those who obtained the greatest benefit were the girls from Mués and Los Arcos as they were the home towns of doña Josefa Ignacia’s first and second husbands respectively.
Keywords: Teaching; Sixteenth-Nineteenth [16th-19th] centuries; Daughters of Charity; Los Arcos (Navarre)